Peningkatan Hasil Belajar Ipa Melalui Pendekatan Kontekstual Pada Materi Bagian- Bagian Tumbuhan Bagi Siswa Kelas IV SD NEGERI 30 Sumpang Bita - Nurazizah Rahayu; Nita Saputri; Reza Arminsyah (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine the increase in science learning outcomes (IPA) in the material of plant parts using a contextual approach (CTL) in class IV students at SD Negeri 30 Sumpang Bita. The research subjects were all 10 grade IV students consisting of 6 male students and 4 female students. This research is a classroom action research by applying the Contextual Teaching and Learning (CTL) approach as an effort to improve science learning outcomes for fourth semester students of SDN 30 Sumpang Bita, Balocci District, Pangkep Regency. Research activities planned as much as 2 cycles. Each cycle of procedures or steps to be carried out consists of 4 main activity components, namely planning, action, observation, and reflection. As for the results of this study, there was an increase in learning outcomes and student activity. It can be seen that there was an increase in learning outcomes for material parts of plants, from an average grade of 60 in the initial conditions, up to 78 in Cycle I, then in Cycle II, it rose to 80 (performance indicator of 80 has been reached). So it can be concluded that learning using the CTL approach can improve learning outcomes and activity in students IV IV SD Negeri 30 Sumpang Bita